(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aims to assess the facilities of Tagaytay Picnic Grove and evaluate their impact on tourist satisfaction, serving as the basis for an improvement plan to enhance visitor experiences. Tagaytay Picnic Grove, a well-known recreational site, attracts a diverse range of tourists seeking leisure, nature, and scenic views. However, the quality and maintenance of facilities—including rest areas, restrooms, picnic spots, and other amenities—greatly influence tourist satisfaction and the destination’s overall reputation. This research employs a quantitative approach using a survey-based method to collect data on tourists’ perceptions and satisfaction levels with the existing facilities. The respondents include 50 tourists visiting Tagaytay Picnic Grove, selected through simple random sampling to ensure representation. The survey questionnaire measures key aspects of facility quality such as cleanliness, accessibility, functionality, and aesthetic appeal. Collected data will be statistically analyzed to identify patterns and correlations between facility conditions and satisfaction levels. Findings are expected to reveal strengths, such as well-maintained facilities that enhance visitor satisfaction, as well as weaknesses, including outdated or insufficient amenities that negatively affect the tourist experience. The results aim to provide a clear understanding of the current condition of facilities at Tagaytay Picnic Grove and their alignment with tourist expectations. Based on these findings, an improvement plan will be developed, focusing on strategic facility upgrades, improved maintenance, and the addition of new amenities. Ultimately, the study seeks to support sustainable tourism development in Tagaytay by enhancing visitor satisfaction, increasing positive feedback, and encouraging repeat visits.